Pengaruh Penggunaan Bahan Ajar Pendidikan Agama Islam dan Budi Pekerti Berbasis Aplikasi Quizizz Terhadap Motivasi Peserta Didik di UPT SMP Negeri 1 Pangkajene Sidrap: The Effect of the Use of Teaching Materials for Islamic Religious Education and Ethics Based on the Quizizz Application on Student Motivation at UPT SMP Negeri 1 Pangkajene Sidrap - Asfiani, Afifah; Rapi, Moh.; Usman (CV. Kalimasada Group, 2024)
This study aims to: 1) Knowing the use of teaching materials for Islamic Religious Education and ethics based on the quizizz application at UPT SMP Negeri 1 Pangkajene Sidrap. 2) Knowing the learning motivation of students at UPT SMP Negeri 1 Pangkajene Sidrap. 3) Knowing the effect of the use of Islamic Religious Education and Ethics teaching materials based on the quizizz application on student learning motivation at UPT SMP Negeri 1 Pangkajene Sidrap. This research is a quantitative research with the type of quasi experiment. With a population of 277 students who were sampled with purposive sampling techniques determined with 60 students divided into experimental groups and control groups. The results obtained in this study indicate that: 1) The use of teaching materials for Islamic Religious Education and ethics based on the quizizz application at UPT SMP Negeri 1 Pangkajene Sidrap is close to 100% in accordance with the steps designed, so it can be said to be running 'Very Well'. 2) The effect of using teaching materials for Islamic Religious Education and Ethics based on the quizizz application on student learning motivation at UPT SMP Negeri 1 Pangkajene Sidrap is obtained through a questionnaire of student learning motivation which is then calculated using a Likert scale which is then measured using the category of the success rate of student learning motivation. Shows the results of 90% which means that the learning motivation of students is in the 'Very Good' category; 3) There is a significant influence on the use of teaching materials for Islamic Religious Education and Budi Pekerti based on the quizizz application, this is indicated by the results of the paired sample t-test data processing which shows that the asymp.Sig value. (2-tailed) of 0.000 or smaller than α 0.05.